Volume 1: Symposia, Parts a and B 2006
DOI: 10.1115/fedsm2006-98359
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery by In-Situ Gas Generation: Volume and Pressure Measurements

Abstract: The experimental studies were conducted to measure the volume and the pressure of the CO2 gas generated according to the new oil recovery technology. An experimental device was designed, built and used for these purposes. The designed setup allowed initiating and controlling the reaction between the “gas-yielding” (GY) and “gas-forming” (GF) agents proposed by this technology. The temperature was controlled, and the generated gas pressure and volume were recorded during the reaction process. The effect of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2, curves 1 and 2). If in the reaction there is diffusion of additional gas into the medium, as noted by the authors Bakhtiyarov et al (2006), Chukwuma (1983), , Riazi (1996), the pressure drop at the final stage of gas release is due to diffusion of gas bubbles from the medium into the liquid. In this case, the ratio of formation and dissolution of gas bubbles is written as follows:…”
Section: Kinetics Of Gas Generationmentioning
confidence: 97%
See 2 more Smart Citations
“…2, curves 1 and 2). If in the reaction there is diffusion of additional gas into the medium, as noted by the authors Bakhtiyarov et al (2006), Chukwuma (1983), , Riazi (1996), the pressure drop at the final stage of gas release is due to diffusion of gas bubbles from the medium into the liquid. In this case, the ratio of formation and dissolution of gas bubbles is written as follows:…”
Section: Kinetics Of Gas Generationmentioning
confidence: 97%
“…Since the 1930s, many studies of the gas diffusion coefficient in liquids have been carried out Bakhtiyarov et al (2006), Chukwuma (1983), Dake (1998), Ferer & Smith (1994), Li & Chen (2023), Mandrik et al (2010), Panakhov & Abbasov (2004), Panakhov & Omrani (2008), . Most of them were carried out using adsorption or diffusion PVT (pressure-volumetemperature) units.…”
Section: Experimental Estimation Of Carbon Dioxide Diffusion In Fluid...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [35], information is provided on an experimental setup that allows one to regulate the reaction temperature and record the volume and pressure of the gas formed. Experimental studies were also carried out on the influence of formation fluid salinity on the parameters (volume and pressure) of the generated gas.…”
Section: Co2 Generation In Reservoir Conditionsmentioning
confidence: 99%
“…Laboratory and field test results showed that additional oil was produced due to application of the in-situ CO 2 system compared with conventional waterflooding. Bakhtiyarov et al [9] investigated the effect of water salinity on gas volume and pressure of the generated CO 2 . Results showed that the intensity of the generated gas increased with water salinity.…”
Section: Introductionmentioning
confidence: 99%